Isolation and Identification of Bacterial Pathogens from Respiratory Tract of Goats - Barde, Preeti; Garg, U.K.; Sharda, R.; Chhabra, Daljeet; Shukla, Supriya (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
A total of 170 samples were examined for bacterial pathogens after staining with Wright’s stain. These included oral swabs, nasal swabs, blood samples, impression smears and tissues from different parts of respiratory tract showing pulmonary lesions. Out of these, only 36 samples (21.17%) collected from clinically ill animals or morbid tissues were showing respiratory tract infection suggestive of respiratory tract infection of bacterial origin which were further processed for microbiological examinations. Pasteurella multocida and E.coli were isolated from 7(19.44%) and 11 samples (30.55%) out of 36 samples respectively in pure culture. The remaining samples did not reveal any bacterial growth.
Keywords: Isolation; E.coli; Pasteurella Multocida